2014
DOI: 10.3906/vet-1310-22
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of conception rates achieved with the transfer of sexed and unsexed bovine embryos

Abstract: Bridges are exposed to various loading conditions, and influence lines have important applications for the design of beams that are subjected to moving loads. The main purpose of this study was to evaluate the applicability of a transfer matrix method (TMM)-based static analysis of monolithic concrete beams with external prestressing cables subjected to moving loads. This approach is important for helping engineers in the preliminary design and is consistent with the design prescriptions of modern codes. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Prior to flushing, each cow received epidural anesthesia (5 to 7 mL of 2% lidocaine; Vilcain, Vilsan, Türkiye). Ova/ embryos were collected non-surgically 6.5 to 7 days after the first TAI using lactated Ringer's solution containing 1% calf serum (CS, N4762; Sigma-Aldrich, USA) and 125 mg/L of kanamycin (Kanovet, Vetaş, Türkiye) [14,15] . Each uterine horn was flushed with 800 to 1000 mL of the solution.…”
Section: Ova/embryo Collectionmentioning
confidence: 99%
“…Prior to flushing, each cow received epidural anesthesia (5 to 7 mL of 2% lidocaine; Vilcain, Vilsan, Türkiye). Ova/ embryos were collected non-surgically 6.5 to 7 days after the first TAI using lactated Ringer's solution containing 1% calf serum (CS, N4762; Sigma-Aldrich, USA) and 125 mg/L of kanamycin (Kanovet, Vetaş, Türkiye) [14,15] . Each uterine horn was flushed with 800 to 1000 mL of the solution.…”
Section: Ova/embryo Collectionmentioning
confidence: 99%
“…About 80% (355,205 embryos) were produced in Brazil and 17% were produced in North America (USA and Canada). While the use of IVF has been increasing greatly around the world, especially in countries such as the United States, Brazil, and Argentina, it is still in the research phase, which is only gradually increasing in Turkey (24,32). Birler et al (33) demonstrated the first IVFproduced healthy live-born lambs at İstanbul University in 2000.…”
Section: Ivf and Embryo Culture (Ivc)mentioning
confidence: 99%